Assessment of the effectiveness of group lending mechanisms to women entrepreneurs in micro finance institutions in Tanzania: The case of pride Tanzania, Morogoro branch - Masimba, G.M (Mzumbe University, 2024)
Dissertation submitted in partial fulfilment of the requirements of the Master’s degree of Business Administration of Mzumbe University